2001
DOI: 10.1177/0899764001303002
|View full text |Cite
|
Sign up to set email alerts
|

Stipended Volunteers: Their Goals, Experiences, Satisfaction, and Likelihood of Future Service

Abstract: Goal setting theory predicts that the initial needs, interests, and aspirations that volunteers bring to organizations are guiding forces in their work behaviors. Other theorists argue that environmental constraints and conditioned responses to positive or negative reinforcement of earlier behaviors are better predictors of subsequent behaviors than initial goals. In this study, the relationship of initial goals to subsequent service outcomes, satisfaction, and intention to volunteer was empirically investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 39 publications
(54 reference statements)
1
57
1
5
Order By: Relevance
“…It is important to stress that the reasons sought are the initial ones and not the current motives for volunteering. Some authors underline that membership and volunteering in an association may change the goals pursued by the individuals (Gidron, 1984;Pearce, 1983;Tschirhart et al, 2001). We thus cannot rule out the possibility that some respondents indicate their current goals, but we have unfortunately no means to detect such cases.…”
Section: The Datamentioning
confidence: 92%
See 2 more Smart Citations
“…It is important to stress that the reasons sought are the initial ones and not the current motives for volunteering. Some authors underline that membership and volunteering in an association may change the goals pursued by the individuals (Gidron, 1984;Pearce, 1983;Tschirhart et al, 2001). We thus cannot rule out the possibility that some respondents indicate their current goals, but we have unfortunately no means to detect such cases.…”
Section: The Datamentioning
confidence: 92%
“…With the same functional approach, Tschirhart et al (2001) obtain five types of goals from items submitted to stipended volunteers who are members of AmeriCorps: (i) the instrumental goal, (ii) the altruistic goal, (iii) the social goal, (iv) the self-esteem goal and (v) the avoidance goal. ''Making new friends'' is one of the two constituent items of the social goal, the other being ''gaining respect of those who value service''.…”
Section: Motives For Volunteering: a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonprofits should learn what volunteers seek from the experience to ensure their satisfaction (Clary, Snyder, and Ridge, 1991;Cnaan and Goldberg-Glen, 1991;Tschirhart and others, 2001). Ferguson (1984) suggested that "other variables related to the relationship might be how much control both parties to the relationship believe they have [and] how power is distributed in the relationship" (p. 20).…”
Section: Satisfactionmentioning
confidence: 99%
“…The findings were that members' satisfaction with their service was very much related to their having specific goals about what they hoped to gain from their experience. The presence of goals is also positively related to the likelihood that national service participants would volunteer in the future (Tschirhart et al, 2001). Neither partisan in intent nor committed to any particular ideology (Simon & Wang, 1999a, 1999b, 2002, national service experiences draw people out of the confines of their usual cultural and economic context and creates the preconditions for participation in politics and civic affairs.…”
mentioning
confidence: 99%